The Effectiveness of Project-Based Learning to Students Ability in Writing Recount Text - Muammar Chadafi; Dea Fatwa Syarifudin (Journal of Education and Religious Studies, 2021)
Teaching English writing for non-native students of senior high schools is not easy. There are several things that must be considered. So that is why the students' writing skill becomes crucial. This study is aimed to know the effectiveness of Project-Based Learning to the students’ ability in writing recount text for the class 10 students of SMK Ma’arif NU Sunan Giri Mulung Driyorejo Gresik. The researcher used a quantitative research reasoning by a pre-experimental design. The population in this research is the class 10 students of the SMK Ma'arif NU Sunan Giri containing 126 students and the sample of this research is 36 students of that class. The instrument was a test that was in form of a pre-test and a post-test after given a treatment. Then data analysis used SPSS by the formula paired sample t-test. This study showed that the average obtained by the post-test was higher than the pre-test. This indicated that the treatment was successful. Paired T-test calculation researcher. T-test was calculated to determine the comparison of the two means between pre-test and post-test. The results were that the value of sig (2-tailed) is 0.001 at the critical value for the 5% level. This means that the significance value is less than 5% or (0.001 <0.05). So, the null hypothesis can be rejected. It can be concluded that the writing the recount text by project-based learning method is effective. Therefore, it was found that 57% of the students underwent the grammar errors. 43% of the students suffered the mechanics errors. The organization of errors happened in 37% of the students’ writing work. 35% of the students faced the vocabulary errors in writing the recount text. So, the future researchers need to take these percentages of the errors into consideration in their research as the students’ difficulties in writing the recount text using project-based learning.